Dukungan Keluarga Pada Pasien Diabetes Mellitus Dalam Upaya Pencegahan Ulkus Diabetikum - Dee, Theodehild M. Theresia; Riantiarno, Flavianus; Sakinah, Siti (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Every patient with diabetes mellitus is at risk of developing diabetic ulcers, a chronic complication resulting from uncontrolled blood glucose levels. Preventive efforts can be achieved through effective self-care management, including blood glucose control, foot care, and regular foot exercises. Family support plays a crucial role in assisting patients with diabetes mellitus to carry out self-care activities, particularly in preventing diabetic ulcers. This study aimed to identify the level of family support among diabetes mellitus patients in efforts to prevent diabetic ulcers in Kupang City. This quantitative descriptive study employed a purposive sampling technique involving 100 diabetes mellitus patients as respondents. Data were collected using a family support questionnaire and analyzed using univariate analysis. The results showed that 47% of patients received moderate family support, 30% received low family support, and only a small proportion received high family support in preventing diabetic ulcers. It can be concluded that nearly half of diabetes mellitus patients in Kupang City receive moderate and low levels of family support. These findings highlight the need to strengthen family involvement in patient care, particularly in preventive measures against diabetic ulcers, through the development of family-based intervention programs. Keywords: Diabetic Foot Ulcer, Prevention, Family Support.  ABSTRAK Tiap pasien diabetes mellitus beresiko mengalami ulkus diabetikum. Dalam upaya pencegahannya, pasien diabetes mellitus dapat melakukan manajemen perawatan diri dalam mengontrol kadar glukosa darah agar tetap terkendali, melakukan perawatan kaki dan senam kaki. Dukungan keluarga merupakan salah satu bagian krusial dalam perawatan pasien diabates mellitus termasuk dalam upaya pencegahan ulkus diabetikum. Penelitian ini bertujuan untuk mengidentifikasi dukungan keluarga pasien diabetes mellitus dalam upaya pencegahan ulkus diabetikum pada di Kota Kupang. Desain penelitian deskriptif kuantitatif dengan teknik sampling purposive sampling. Terdapat 100 pasien diabetes mellitus di Kota Kupang yang menjadi responden dalam penelitian ini. Pengumpulan data menggunakan kuesioner dukungan keluarga, kemudian data dianalisis dengan analisis univariat. Analisis menunjukkan hampir dari setengahnya pasien diabetes mellitus memiliki dukungan keluarga cukup (47 %) dan dukungan keluarga kurang (30 %), sebagian kecil mendapatkan dukungan keluarga dalam melakukan pencegahan ulkus diabetikum. Dapat disimpulkan hampir setengah dari pasien diabetes mellitus mendapatkan dukungan keluarga yang cukup dan kurang. Temuan ini dapat dijadikan acuan bagaimana mengembagkan intervensi yang melibatkan keluarga secara aktif dalam proses perawatan pasien termasuk dalam upaya pencegahan ulkus diabetikum. Kata Kunci: Ulkus Diabetikum, Pencegahan, Dukungan Keluarga.